CT and MR Unilateral Brain Features Secondary to Nonketotic Hyperglycemia Presenting as Hemichorea-Hemiballism - Víctor Manuel Suárez-Vega; Carlos Sánchez Almaraz; Ana Isabel Bernardo; Ricardo Rodríguez-Díaz; Ana Díez Barrio; Leticia Martín Gil (Case Reports in Radiology)
Hemichorea-hemiballism is an unusual hyperkinetic movement disorder characterized by continuous involuntary movements of an entire limb or both limbs on one side of the body. The acute onset of this disorder occurs with an insult in contralateral basal ganglia. Ischemic events represent the most common cause. Nonketotic hyperglycemia comes in second place. Nonketotic hyperglycemic hemichorea-hemiballism (NHH) is a rare cause of unilateral brain abnormalities on imaging studies confined to basal ganglia (mainly putaminal region as well as caudate nucleus). Subtle hyperdensity in striatal region can be found on CT studies whereas brain MR imaging typically shows T1 hyperintensity and T2 hypointensity in the basal ganglia contralateral to the movements. Diagnosis is based on both glucose levels and neuroimaging findings. Elevated blood glucose and hemoglobin A1c levels occur with poorly controlled diabetes. In this case report, our aim is to present neuroimaging CT and MR unilateral findings in an elderly woman secondary to nonketotic hyperglycemia presenting as hemichorea-hemiballism.